On-scene alternatives for emergency ambulance crews attending patients who do not need to travel to the accident and emergency department: a review of the literature. Issue 2 (26th February 2004) - Snooks, H A; Dale, J; Hartley-Sharpe, C; Halter, M
Abstract : With rising demand and recognition of the variety of cases attended by emergency ambulance crews, services have been considering alternative ways of providing non-urgent care. This paper describes and appraises the research literature concerning on-scene alternatives to conveyance to an emergency department, focusing on the: (1) profile and outcomes of patients attended but not conveyed by emergency crews; (2) triage ability of crews; (3) effectiveness and safety of protocols that allow crews to convey patients to alternative receiving units or to self care. The literature search was conducted through standard medical databases, supplemented with manual searches. Very few "live" studies were identified, and fewer still that included a control group. Findings indicated a complex area, with the introduction of protocols allowing crews to leave patients at scene carrying clinical risk. Robust research evidence concerning alternatives to current emergency care models is needed urgently to inform service and practice development.